PERSEPSI MAHASISWA UKIM TERHADAP PILPRES 2024 (STUDI KOMPARATIF ANTARA MAHASISWA FISIP DENGAN MAHASISWA FAKULTAS HUKUM UKIM) - Maswekan, Max; Basuki, Eko; Tamaela, Vesticha Marshanda; Tetkiasa, Mario Paulus (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The presidential elections held every five years are a democratic process mandated by the Constitution (1945 Constitution), which is elaborated and regulated in Law Number 7 of 2017 on General Elections. Pemilihan presiden yang diadakan setiap lima tahun telah dilaksanakan sebanyak 12 kali sejak kemerdekaan Indonesia. In the 2024 elections, held on February 14, representatives (legislative) as well as the President and Vice President will be elected. This research specifically aims to understand the differences in perceptions among students from three Study Programs (Prodi), namely the Social Welfare and Communication Studies Programs at the Faculty of Social and Political Sciences, and the Law Studies Program at the Faculty of Law, Christian University of Indonesia Maluku (UKIM), regarding the differences in perceptions of the Presidential Election, whether its implementation is in accordance with the mandate of the law, democratic, of high quality, and whether the political system adopted in Indonesia is suitable and ideal. The method used is a mixed method (qualitative and quantitative) with a comparative approach. The results obtained show significant differences in perception, both quantitatively and qualitatively, among the three study programs.